Implementasi Program Bantuan Ketahanan Pangan melalui Penyaluran Bantuan Hewan Ternak dan Bibit Tumbuhan di Desa Bangun Purba - Rodhiatun Nazliah Damanik; Muhammad Arifin Nasution (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
Food security is a crucial foundation in breaking the cycle of poverty, particularly in rural areas that are vulnerable to limited food access. The Government of Bangun Purba Village has implemented a food security assistance program through the distribution of livestock and crop seedlings as a strategy to improve both food availability and community income. This study aims to describe the implementation process of the program, identify supporting and inhibiting factors, and assess its impact on poverty alleviation in the village. The research employs a descriptive qualitative approach with data collected through interviews, observation, and documentation. Informants include the village head, program coordinator, members of the Village Consultative Body (BPD), and program beneficiaries. Data analysis is based on David C. Korten’s Theory of Successful Program Implementation, which encompasses three main indicators: the program, implementing organization, and target group. The results show that the food security program in Bangun Purba Village has contributed positively to improving food availability for some community members. However, its effectiveness has not yet reached an optimal level due to uneven distribution of aid, lack of technical assistance, limited socialization, and weak coordination among stakeholders.